Effects of Withdrawal of a Performance-Contingent Reward on Supervisory Influence and Power - Greene, Charles N.; Podsakoff, Philip M. (Academy of Management Journal, 1981)
A field experiment was conducted to investigate effects of removal of a performance-contingent reward on subordinates? perceptions of their supervisors? sources of influence. A significant increase was found in perceptions of supervisors? use of punishment, but reward, referent, and organizationally-sanctioned power declined significantly. Expert power was unaffected by removal of the incentive system.